2001
DOI: 10.1073/pnas.111155798
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB is required for hypertrophic growth of primary rat neonatal ventricular cardiomyocytes

Abstract: The transcription factor NF-B regulates expression of genes that are involved in inflammation, immune response, viral infection, cell survival, and division. However, the role of NF-B in hypertrophic growth of terminally differentiated cardiomyocytes is unknown. Here we report that NF-B activation is required for hypertrophic growth of cardiomyocytes. In cultured rat primary neonatal ventricular cardiomyocytes, the nuclear translocation of NF-B and its transcriptional activity were stimulated by several hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
234
3
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(251 citation statements)
references
References 59 publications
(102 reference statements)
10
234
3
4
Order By: Relevance
“…Furthermore, the NF B dimer ratio has been shown to determine the ultimate level of target gene expression (18,22). NF B-mediated gene transcription has been proposed in models of myocardial diseases (3,77,78). Taken together with the previous finding that elevated levels of Myo/V1 are found in failing mammalian hearts (5,6), this study collectively suggests that Myo/V1 might play a significant NF B regulatory role at the transcriptional level during chronic pathophysiological conditions such as human heart failure.…”
Section: Figsupporting
confidence: 57%
“…Furthermore, the NF B dimer ratio has been shown to determine the ultimate level of target gene expression (18,22). NF B-mediated gene transcription has been proposed in models of myocardial diseases (3,77,78). Taken together with the previous finding that elevated levels of Myo/V1 are found in failing mammalian hearts (5,6), this study collectively suggests that Myo/V1 might play a significant NF B regulatory role at the transcriptional level during chronic pathophysiological conditions such as human heart failure.…”
Section: Figsupporting
confidence: 57%
“…Recent studies have suggested that NF-κB signaling seems to be involved in a number of cytokines gene expressions, and development of cardiac hypertrophy in vivo and in vitro conditions (18,26). The exact intracellular mechanisms underlying the activation of cytokines in mice lacking NPRA are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a number of genes altered by HS diet were normalized by PC including the myosin heavy-chain isoform switch characteristic of loaddependent hypertrophy (10,14). Changes in ␣-tropomyosin and in the NF-B pathway, which have been linked with ventricular hypertrophy (31,32), were also positively modified by PC. This is consistent with the finding that 1,25(OH) 2 D 3 significantly blunts the activation of NF-B signaling in vitro (33).…”
Section: Discussionmentioning
confidence: 99%